PENGARUH BUDAYA ORGANISASIONAL, MOTIVASI KERJA, DAN KEPEMIMPINAN TERHADAP KINERJA (Studi pada Guru Sekolah Menengah Pertama Negeri di KecamatanPemalang, Kabupaten Pemalang) - Nuzulia Rahma Arivina, 12.05.51.0170; ., Muhaimin (Students Journal of Economic and Management, 2016)
This research is analyzing the effect of Organizational Culture, Work Motivation, and Leadership on Performance. The researchâs object is the Junior High School in Pemalang districts, Pemalang. This topic was taken because of the lack of student competition in academic at Junior High School in Pemalang Districts, Pemalang which indicates the performance of teachers is still low. This researchâs population are all teachers of Junior High School in Pemalang district, Pemalang who numbered 301 teachers come from eight school. The sampling techniques of this research is using purposive sampling, then continued by quota random sampling. When collecting data, writers use questionnaire to get information from respondents. The purpose of this research is to find the answers from variableâs effect on teacherâs performance. Data were collected then analyzed by Product Moment Correlation for validity test of the questionâs item, cronbachâs alpha for realibility test, regression test get the result of the effect from each independent variables on dependent variable either partially or simultaneously. The result of this research are : (1) Organizational culture has a positive and significant impact on teacher performance. (2) Work motivation has a positive and significant impact on teacher performance. (3) Leadership has a positive and significant impact on teacher performance. Keyword : Organizational Culture, Work Motivation, Leadership, Perfomance